Evaluation of an overnight non-culture test for detection of viable Gram-negative bacteria in endoscope channels - Singh, Harminder; Duerksen, Donald R.; Schultz, Gale; Reidy, Carol; DeGagne, Pat; Olson, Nancy; Nugent, Zoann; Alfa, Michelle J. (Endoscopy International Open, 2019)
Background and study aims Prevention of infection transmission from contaminated endoscopes would benefit from a rapid test that could detect low levels of viable bacteria after high level disinfection. The aim of this study was to evaluate the rapid NOW! (RN) test’s ability to detect endoscope contamination.Materials and methods The RN test kit and the accompanying fluorometer were evaluated. The manufacturer states that a fluorometer signal > 300 units is indicative of viable Gram-negative bacteria. Suspension testing of varying concentrations of Escherichia coli, Pseudomonas aeruginosa and Enterococcus faecalis were used to determine the RN test limit of detection. Simulated-use testing was done using a duodenoscope inoculated with 10 % blood containing approximately 35 CFU E. coli per channel. Samples were extracted from the duodenoscope instrument channel and tested using the manufacturer’s instructions.Results The RN test could consistently detect 10 CFU of E. coli and P. aeruginosa (fluorescent signal of 9,000 to 11,000 units) but not E. faecalis. Sensitivity and specificity for Gram-negative bacteria were 93 % and 90 %, respectively, using all of the suspensions in the study. Extraction of E. coli from an inoculated duodenoscope instrument channel repeatedly provided a positive signal (i. e. > 2,000 units).Conclusions The RN test can reliably detect low levels of Gram-negative bacteria in suspension as well as from samples extracted from endoscope channels. These preliminary findings are encouraging but further assessment of extraction efficacy, impact of organic residuals and clinical workflow are still needed.